Rebound Thrombocytosis after Induction Chemotherapy is a Strong Biomarker for Favorable Outcome in AML Patients. Issue 2 (April 2019) - Schnell, Bianca R.; Seipel, Katja; Bacher, Ulrike; Jeker, Barbara; Mueller, Beatrice U.; Banz, Yara; Novak, Urban; Pabst, Thomas
Abstract : Abstract: Whereas the molecular events underlying acute myeloid leukemia (AML) are increasingly identified, dynamics of hematologic recovery following induction chemotherapy remain mysterious. Platelet recovery may vary between incomplete and excess recovery among patients achieving remission. We analyzed platelet recovery after the first induction cycle in 291 consecutive AML patients. We defined excess platelet rebound (EPR) as platelet increase above 500 G/L. We observed EPR in 120 (41.2%) patients. EPR+ patients had lower platelets at diagnosis, higher marrow infiltration, more frequently NPM1 mutations, and were associated with ELN favorable risk. Absence of EPR correlated with complex karyotypes, ELN intermediate-I and adverse risk, and therapy-related AML. Overall survival was better in EPR+ patients than EPR- (median 125 vs 41 months; p = 0.04), as was disease-free survival. By multivariate analysis, EPR+ was an independent parameter associated with favorable survival. Plasma thrombopoietin (TPO) levels at diagnosis indicated EPR+ (p < 0.0001), while GATA-1, GATA-2, and MPL mRNA expression did not differ between EPR+ and EPR- patients. Finally, transcription factors blocking early megakaryopoiesis were upregulated in EPR- patients, while NFE2 involved in late megakaryocyte differentiation was increased in EPR+ patients. Our work identifies mechanisms involved in platelet recovery after induction chemotherapy. Abstract : Supplemental Digital Content is available in the text